Orbital-selective effect of spin reorientation on the Dirac fermions in a non-charge-ordered kagome ferromagnet Fe3Ge - Rui Lou; Liqin Zhou; Wenhua Song; Alexander Fedorov; Zhijun Tu; Bei Jiang; Qi Wang; Man Li; Zhonghao Liu; Xuezhi Chen; Oliver Rader; Bernd Büchner; et al. (Nature Communications)
Abstract Kagome magnets provide a fascinating platform for the realization of correlated topological quantum phases under various magnetic ground states. However, the effect of the magnetic spin configurations on the characteristic electronic structure of the kagome-lattice layer remains elusive. Here, utilizing angle-resolved photoemission spectroscopy and density functional theory calculations, we report the spectroscopic evidence for the spin-reorientation effect of a kagome ferromagnet Fe3Ge, which is composed solely of kagome planes. As the Fe moments cant from the c-axis into the a b plane upon cooling, the two kinds of kagome-derived Dirac fermions respond quite differently. The one with less-dispersive bands (k z   ~  0) containing the $$3{d}_{{z}^{2}}$$ 3 d z 2 orbitals evolves from gapped into nearly gapless, while the other with linear dispersions (k z  ~ π) embracing the 3d x z /3d y z components remains intact, suggesting that the effect of spin reorientation on the Dirac fermions has an orbital selectivity. Moreover, we demonstrate that there is no signature of charge order formation in Fe3Ge, contrasting with its sibling compound FeGe, a newly established charge-density-wave kagome magnet.